Euro-Par 2013: Parallel Processing Workshops: BigDataCloud, DIHC, FedICI, HeteroPar, HiBB, LSDVE, MHPC, OMHI, PADABS, PROPER, Resilience, ROME, and UCHPC 2013, Aachen, Germany, August 26 - 27, 2013. Revised Selected Papers - Mey, Dieter (Lecture notes in computer science, 2014)
This book constitutes thoroughly refereed post-conference proceedings of the workshops of the 19th International Conference on Parallel Computing, Euro-Par 2013, held in Aachen, Germany in August 2013. The 99 papers presented were carefully reviewed and selected from 145 submissions. The papers include seven workshops that have been co-located with Euro-Par in the previous years: - BigDataCloud (Second Workshop on Big Data Management in Clouds) - HeteroPar (11th Workshop on Algorithms, Models and Tools for Parallel Computing on Heterogeneous Platforms) -HiBB (FourthWorkshop on High Performance Bioinformatics and Biomedicine) -OMHI (Second Workshop on On-chip Memory Hierarchies and Interconnects) -PROPER (Sixth Workshop on Productivity and Performance) -Resilience (SixthWorkshop on Resiliency in High Performance Computing with Clusters, Clouds, and Grids) -UCHPC (Sixth Workshop on UnConventional High Performance Computing) as well as six newcomers: -DIHC (First Workshop on Dependability and Interoperability in Heterogeneous Clouds) -FedICI (First Workshop on Federative and Interoperable Cloud Infrastructures) -LSDVE (First Workshop on Large Scale Distributed Virtual Environments on Clouds and P2P) -MHPC (Workshop on Middleware for HPC and Big Data Systems) -PADABS ( First Workshop on Parallel and Distributed Agent Based Simulations) -ROME (First Workshop on Runtime and Operating Systems for the Manycore Era) All these workshops focus on promotion and advancement of all aspects of parallel and distributed computing
Literaturangaben
Keywords: Konferenzschrift -- 2013 -- Aachen; Konferenzschrift; Cloud Computing; Parallelverarbeitung; Hochleistungsrechnen